pH-dependent interactions of coacervate-forming histidine-rich peptide with model lipid membranes - Gudlur, Sushanth; Ferreira, Filipe Viana; Ting, Javier Shu Ming; Domene, Carmen; Maricar, Syed; Le Brun, Anton P.; Yepuri, Nageshwar; Moir, Michael; Russell, Robert; Darwish, Tamim; Miserez, Ali; Cárdenas, Marité (Frontiers in Soft Matter, 2024)
Peptide-based liquid droplets (coacervates) produced by spontaneous liquid-liquid phase separation (LLPS), have emerged as a promising class of drug delivery systems due to their high entrapping efficiency and the simplicity of their formulation. However, the detailed mechanisms governing their interaction with cell membranes and cellular uptake remain poorly understood. In this study, we investigated the interactions of peptide coacervates composed of HBpep-peptide derived from the histidine-rich beak proteins (HBPs) of the Humboldt squid-with model cellular membranes in the form of supported lipid bilayers (SLBs). We employed quartz crystal microbalance with dissipation monitoring (QCM-D), neutron reflectometry (NR) and atomistic molecular dynamics (MD) simulations to reveal the nature of these interactions in the absence of fluorescent labels or tags. HBpep forms small oligomers at pH 6 whereas it forms µm-sized coacervates at physiological pH. Our findings reveal that both HBpep oligomers and HBpep-coacervates adsorb onto SLBs at pH 6 and 7.4, respectively. At pH 6, when the peptide carries a net positive charge, HBpep oligomers insert into the SLB, facilitated by the peptide's interactions with the charged lipids and cholesterol. Importantly, however, HBpep coacervate adsorption at physiological pH, when it is largely uncharged, is fully reversible, suggesting no significant lipid bilayer rearrangement. HBpep coacervates, previously identified as efficient drug delivery vehicles, do not interact with the lipid membrane in the same manner as traditional cationic drug delivery systems or cell-penetrating peptides. Based on our findings, HBpep coacervates at physiological pH cannot cross the cell membrane by a simple passive mechanism and are thus likely to adopt a non-canonical cell entry pathway.